Highly Stretchable and Conductive Self-Healing Hydrogels for Temperature and Strain Sensing and Chronic Wound Treatment - Zhang, Jieyu; Wu, Can; Xu, Yuanyuan; Chen, Jiali; Ning, Ning; Yang, Zeyu; Guo, Yi; Hu, Xuefeng; Wang, Yunbing (ACS applied materials & interfaces, 2020)
Flexible bioelectronics for biomedical applications requires a stretchable, conductive, self-healable, and biocompatible material that can be obtained by cost-effective chemicals and strategies. Herein, we synthesized polypyrrole or Zn-functionalized chitosan molecules, which are cross-linked with poly(vinyl alcohol) to form a hydrogel through dynamic di-diol complexations, hydrogen bonding, and zinc-based coordination bonds. These multiple dynamic interactions endow the material with excellent stretchability and autonomous self-healing ability. The choice of Food and Drug Administration (FDA)-approved materials (poly(vinyl alcohol) and chitosan) as the matrix materials ensures the good biocompatibility of the hydrogel. The conductivity contributed by the polypyrrole allowed the hydrogel to sense strain and temperature, and the coordinated Zn significantly enhanced the antibacterial activity of the hydrogel. Moreover, using a diabetic rat model, we have proved that this hydrogel is capable of promoting the healing of the infected chronic wounds with electrical stimulation.